THE CURRENT STATUS OF BIODIESEL PRODUCTION TECHNOLOGY: A REVIEW - Rizal Alamsyah; Armansyah H. Tambunan; Y. Aris Purwanto; Dadan Kusdiana (PERTETA, 2007)
ABSTRACTBiodiesel is addressed to the name of fuel which consist of mono-alkyl ester that made from renewable and biodegradable resources, such as oils from plants (vegetable oils), waste or used cooking oil, and animal fats. Such oils or fats are chemically reacted with alcohols or methanol In producing chernical compounds called fatty acid methyl ester (FAME) and these reactions are called transesterification and esterification. Glycerol, used in the pharmaceutical and cosmetics industry is produced from biodiesel production as a by-product. Researches on biodiesel as an alternative petroleum diesel have been done for more than 20 years. Transesterification reaction can be acid-catalyzed, alkali-catatyzed, or enzyme-catalyzed. Commercially biodiesel is processed by transesterification with alkali catalyst. This process, however, requires refining of products and recovery of catalysts, Such biodiesel production accelerates researches on biodiesel to obtain simpler methods, better quality. and minimum production cost. Besides the catalytic production for biodiesel, there is a method for biodiesel production namely non-catalytic production. Non-catalytic transesterification method was developed since catalytic tranestertfification still has two main problems assoclated With long reaction time and complicated purification. The first problem occurres because of the two phase nature of vegetable oil/methanol mixture, and the last problem is due to purification of catalyst and glycerol. The application of catalytic tranestertfication method leads to condition of high biodiesel production cost and high energy consumption. This paper provides information of biodiesel production progress namely catalytic tranestertfification (acid, alkali, and enzymatic tranesterfification), and non-catalytic tranesterification (at sub-critical-supercritical temperature under pressurized conditions). It was found that every method of biodiesel production still has advantages and disadvantages. It means that there is a necessity to develop biodiesel processing method further in order to obtain high reaction rate, high reaction constant (k), high yield, safely process, and minimum energy consumption. In conclusion. there are some works should be undertaken in biodiesel research. Keywords: biodiesel, methyl esters, transesterification. estenfication, and FAME Diterima: 31 Oktober 2007: Disetujui: 11 Desember 2007